Establishment of valnemulin susceptibility breakpoint against Clostridium perfringens in rabbits. (December 2017) - Tao, Meng-Ting; Zhou, Yu-Feng; Sun, Jian; Liu, Ya-Hong; Liao, Xiao-Ping
Abstract: Susceptibility breakpoints provide fundamental information for rational administration of antibiotics. The present investigation reports the first valnemulin susceptibility breakpoint (MIC<0.25 μg/mL) against Clostridium perfringens infections in rabbits based on the wild-type cutoff (COWT ) and the pharmacokinetics/pharmacodynamic (PK/PD) cutoff (COPD ). The established susceptibility breakpoint of valnemulin might be useful in resistance surveillance of pleuromutilins and development of clinical breakpoints. Highlights: We summarized the MIC distribution of valnemulin against rabbit C. perfringens. Pharmacokinetics of valnemulin in rabbit intestinal tract was reported. We established the COWT and COPD levels for valnemulin against C. perfringens. The established breakpoint will be useful in pleuromutilin resistance surveillance.